Ergonomic Design Chair For Postpartum Mothers - Sumaidy, Eliyana Sari (2016)
This study was carried out in the Ayer Keroh Health Clinic following registration with the National Medical Research Register (NMRR). Its objective is to address the concerns faced by postpartum mothers while being seated in the waiting area of the clinic because of pain at in their episiotomy wound. The problem areas were identified, which included the technical requirements needed by postpartum mothers in designing an ergonomic chair. A new design feature(s) was included in the chair, and then corroborated with regards to feasibility and usability. Considering the technical requirements, a questionnaire is conducted and data analysis is done utilising AHP and HOQ. The chosen design from the three conceptual designs was conceived in the Solidworks software. For chair dimensions, the 5th, 50th and 95th percentile is computed using Minitab17 from the anthropometry measurements of postpartum mothers. The CES edupack is utilised for choosing material for specific parts of the chair. Attributes of an ergonomic chair include simple to use and adjustable armrest, comfort and ease of cleaning. The corroboration was done with respect to the technical method by utilising pressure mapping and subjective methodology from the survey. The comparison of respondents’ contact pressure is done using the present chair in the clinic’s waiting area and the model of the ergonomic chair. It was noted that the contact pressure decreased at the perineal area. The projected outcome from the chair design is able to scrutinise the postpartum mothers’ technical requirements and the ergonomic chair’s designs will decrease the episiotomy wound. This research could undergo further scrutiny in terms of designing an ergonomic chair which is apt for postpartum mothers and offers comfort to 95 percent of users. Going forward, the chair should be designed with an adjustable height and in accordance with body dimensions of postpartum mothers, from 1st percentile to 99th percentile for greater comfort.